The Effect of Health Education on Knowledge and Attitudes of Hand Washing in Children at TKA-TPA Al Muhajirin Kampung Parang - Aulya Kartini Dg Karra; Helmi Juwita (Faculty of Nursing and Midwifery, Binawan University, 2023)
Health problems in children are related to the habit of not keeping their hands clean. The lack of hand washing behavior in school age children is caused by low knowledge about hand washing. Health education is an effort to modify behavior through increasing knowledge and skills to improve healthier lifestyles. The purpose of this study was to identify the effect of health education on the level of knowledge and attitudes towards hand washing in children. This type of quantitative research with a Quasi Experiment approach. Research design one group prepost test design. The sample of this study were 20 children out of a total of 20 children at TKA-TPA Al Muhajirin Kampung Parang. The research instrument used a research questionnaire on the level of knowledge and hand washing attitudes. Statistical test using paired t test. The research results showed that the level of knowledge before the intervention was 18 and increased to 19.45 after the intervention. There was a difference in the average level of knowledge between before and after the intervention with an average difference of 1.45 and a p value = 0.000. Variable hand washing attitude, the table shows that the average hand washing attitude indicator of action before the intervention was 18 and increased to 19 after the intervention. There is a difference in the average action between before and after the intervention with a mean rank difference of 1 and a value of p = 0.001. This means that providing health education about hand washing attitudes is effective in increasing hand washing attitudes in children, where there is a significant increase